Strength and power characteristics of elite junior and senior rugby league athletes - Wade, J.; Fuller, J.; Drummond, S.; Devlin, P.; Doyle, T. (Journal of Australian Strength and Conditioning, 2017)
Strength and conditioning coaches play an important role in developing the physical attributes required for sport while athletes are progressing through the developmental years. Strength and power are important characteristics for performance in rugby league. The purpose of this study was to provide a lower body strength and power profile of elite junior (aged 17-20 years) and elite senior (open-aged professional) rugby league athletes within their respective player positions groups. In doing this, the research will provide practitioners with improved understanding of what physical attributes should be targeted in an appropriate athletic development program for 17-20 year old elite rugby league athletes.